Perfil redox, imunológico e histopatológico de jundiás infectados por Aeromonas hydrophila e tratados com extrato de folhas de Hesperozygis ringens (Benth.) Epling - Rosa, Isadora Aguirre (2024)
Aquaculture represents an essential practice for feeding the growing world population and has demonstrated record expansion levels. Combined with this growth, bacterial outbreaks have emerged and lead to large losses in this sector. Aeromonas hydrophila is one of the main pathogens in fish farming, with multifactorial virulence, multiresistant to drugs, including approved antimicrobials, and capable of affecting several species of fish, especially silver catfish (Rhamdia quelen). Although effective and widely used, available antimicrobials have adverse effects on fish and can accumulate in the aquatic environment and in their meat, posing a risk to the health of these animals, humans and the environment. Given this fact, the search for therapeutic alternatives is necessary and constant. The species Hesperozygis ringens (Benth.) Epling (Lamiaceae) has antimicrobial, larvicidal, antiparasitic and anesthetic properties applicable to fish farming. The hexane extract of leaves of this species (HEHR) significantly increased the survival rate of silver catfish challenged with A. hydrophila. For this reason, the objective was to evaluate the redox, immunological and histological profile of healthy silver catfish or those experimentally infected by A. hydrophila and treated with HEHR, to elucidate its action on such pharmacological targets. The extract was obtained by extraction in a Soxhlet apparatus and lyophilized. After acclimatization, silver catfish were subjected to an injection containing a suspension of A. hydrophila MF 372510 or saline, and treated through a single immersion bath. Consecutively, the level of lipid hydroperoxides (LOOH), activity of catalase (CAT) and glutathione S-transferase (GST) enzymes, and total antioxidant capacity in the muscle and liver of silver catfish were evaluated 4- and 7- days post-infection (DPI). Posteriorly, the hemolytic activity of the complement system and the activity of the enzymes lysozyme and myeloperoxidase were determined in the serum of silver catfish 7 DPI, and the gills and liver of these fish were histologically analyzed. Florfenicol (4 mg/L) (FLOR4) and HEHR15 (15 mg/L) treatments demonstrated pro-oxidant and immunosuppressive effects in the presence of A. hydrophila infection. FLOR30 (30 mg/L) did not demonstrate immunostimulating or immunosuppressive effects in infected silver catfish, however immunosuppression was verified in healthy silver catfish, also verified for FLOR4. HEHR30 (30 mg/L) did not induce lipid peroxidation, nor did it harm the antioxidant defenses of healthy silver catfish, and it did not act as a pro-oxidant agent in infected silver catfish. This treatment provided a significant increase in hepatic CAT activity 4 DPI. The architecture of the liver tissue was preserved, but slight epithelial detachment in the gills was observed in healthy or infected silver catfish treated with HEHR30. No treatment was able to prevent histological liver damage caused by A. hydrophila. HEHR30 did not demonstrate deleterious effects on the innate immune system of healthy or infected silver catfish. Therefore, HEHR30 is a safer natural product compared to FLOR, and is characterized as a promising antimicrobial alternative for future investigations aimed at treating bacterioses caused by A. hydrophila, given the increase in the incidence of microbial resistance to drugs used in fish farming, in addition to being an extract that did not cause immunosuppression, nor did it cause pro-oxidants effects in silver catfish, and is composed of biodegradable constituents.